2021
DOI: 10.5465/amj.2018.1487
|View full text |Cite
|
Sign up to set email alerts
|

The Catch-22 of Countering a Moral Occupational Stigma in Employee-Customer Interactions

Abstract: Past research suggests that individuals in dirty work occupations can manage their self-views so as to derive positive self-definitions that allow them to perform their tasks with less of the burden of stigma. Results from our three studies show that this may not necessarily be the case when they try to manage how occupational outsiders view them. Findings from our studies show that in terms of this external perspective, rather than thwarting the occupational stigma, active stigma management by the stigma bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 105 publications
0
27
0
Order By: Relevance
“…Similar to studies at the individual level, studies of occupational stigma have largely left processes of stigmatization unexamined or treated them as implicit. Two forthcoming papers are exceptions: one discusses how coping may inadvertently maintain stigmatization for occupational members (Mikolon, Alavi, & Reynders, 2020), and the other examines the emergence of professional stigma after ethical transgression (Wang, Raynard, & Greenwood, 2020).…”
Section: Occupational Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to studies at the individual level, studies of occupational stigma have largely left processes of stigmatization unexamined or treated them as implicit. Two forthcoming papers are exceptions: one discusses how coping may inadvertently maintain stigmatization for occupational members (Mikolon, Alavi, & Reynders, 2020), and the other examines the emergence of professional stigma after ethical transgression (Wang, Raynard, & Greenwood, 2020).…”
Section: Occupational Levelmentioning
confidence: 99%
“…For example, Mikolon et al (2020) showed that frontline workers' stigma management tactics inadvertently reinforce the occupational moral stigma perceived by customers. Notably, five of the six management strategies in our framework (i.e., boundary management, dilution, information management, cooptation, and emotion work) could potentially contribute to the maintenance of stigmatization.…”
Section: Maintenancementioning
confidence: 99%
“…The present study concluded that occupational stigma consciousness negatively impacts work-related outcomes, such as occupational stress and burnout (Clough et al, 2020). Previous literature suggests that occupational stigma has a negative impact on employees in terms of cognition and behavior (Mikolon et al, 2021;Shigihara, 2018). From a behavioral perspective, occupational stigma consciousness leads to absenteeism and turnover (Sommerland et al, 2017;Campbell, 2020).…”
Section: Occupational Stigma Consciousness and Workplace Deviant Beha...mentioning
confidence: 53%
“…, 2020). Previous literature suggests that occupational stigma has a negative impact on employees in terms of cognition and behavior (Mikolon et al , 2021; Shigihara, 2018). From a behavioral perspective, occupational stigma consciousness leads to absenteeism and turnover (Sommerland et al.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation